Analisis Faktor-Faktor Yang Mempengaruhi Minat Belajar Mahasiswa di Masa Pandemi Pada Mata Kuliah Penulisan Karya Ilmiah di Universitas Muhammadiyah Sumatera Utara - Silvia Febrianti; Hani Nursafwa; Bustanul Arifin; Isra Hayati; Zailani Zailani (Al-Ulum: Jurnal Pendidikan Islam, 2021)
Online learning is one solution of teaching and learning activities continue to be carried out during the COVID-19 pandemic. But, in this case online learning activities have some obstacles that makes some college students have the wane of their interest in learning. Interest is a willingness of one's soul to carry out activities happily that make a changes in knowledge, skills and behavior.  The formulation of the problem related to this research is the decreased interest of college students in online learning at the course of writing scientific papers.  While the purpose of this study is to analyze the factors that influence college students’ interest in learning at the course of writing scientific papers during a pandemic.  In this article, the method used by the author is a qualitative method with interviews and observations of fourth semester students of class A1 morning Islamic religious education study program.  Based on the results of interviews and observations made to 8 college students, there are 2 people whose interest in learning is stable, while the other 6 college students' interest in learning decreases.  The factors that influence college students’ learning interest are 1) Internet network 2) Media and learning resources 3) Communication 4) Environment. For this reason, every college students must prepare adequate facilities and infrastructure and motivate themselves to learn too.Keyword: Influencing Factors, Interest in Learning, Pandemic